Development Of A Wordwall-Assisted Pancasila Education E-Book To Enhance Students’ Tolerance And Learning Interest: Pengembangan E-Book Pendidikan Pancasila dengan Bantuan Wordwall untuk Meningkatkan Toleransi dan Minat Belajar Siswa - ramadhani, indri; Nursalam, Nursalam; Azis, Abdul (Pedagogia : Jurnal Pendidikan, 2026)
General Background: Pancasila education is essential for developing students’ character, particularly tolerance in multicultural contexts. Specific Background: In elementary schools, learning still relies on conventional methods with limited digital media, resulting in low student engagement and inadequate development of tolerance and learning interest. Knowledge Gap: Previous studies mainly emphasize cognitive outcomes, while the integration of Wordwall with e-book media for character development remains limited. Aims: This study aims to develop a Wordwall-assisted Pancasila Education e-book and evaluate its feasibility, practicality, and outcomes on students’ tolerance and learning interest. Results: Using the ADDIE-based Research and Development approach, the e-book demonstrates interactive, collaborative, and contextual features through reflection, discussion, and game-based activities. Expert validation and user responses indicate that the product is valid and practical. The implementation shows increased student participation, respect for differences, and learning motivation compared to conventional methods. Novelty: The study proposes an integrated digital learning model combining Wordwall and e-book media to support both cognitive and character development. Implications: The findings indicate that interactive digital media integrated with character-based content can support meaningful learning and foster affective and cognitive outcomes in elementary education. KeywordsPancasila Education; Digital Learning Media; Wordwall; Tolerance Character; Learning Interest Highlights• Interactive digital module integrates game-based activities with character learning• Student participation and respect for diversity increase in classroom activities• Validation and user responses indicate high usability in elementary settings